NUMERICAL STUDY OF AUTOMOBILE FRONT-WINDSHIELD DEFROSTING - ZHAO LinLin; FAN PingQing; WANG YanSong (Jixie qiangdu)
RNGk-ε turbulence model was chosen to analyze the defrosting of automobile front-windshield. To research the influences of computational domain on simulation results,the front B-pillar part of cabin and full-scale crew cabin models were established respectively. The both models contained the driver,passenger and seats to ensure accuracy. During the simulation,the driver and passenger were considered as heat sources. The results show that,simulation convergence time of full-scale crew cabin increases 44% than the front B-pillar cabin’s,but two models’ differences in air flow distribution and steady wind speed are very small. Besides,there are obvious differences in average temperature of windshield and liquid fraction of frost layer. In transient simulation of defrosting,the full-scale crew cabin is better compared with the experiment. In addition,the simulation results of full-scale crew cabin can reflect the temperature of driver’s breath point accurately. Therefore,the forward B-pillar of crew cabin can be used to study the air flow distribution of defrost duct. But when studying defrosting transient effect or evaluating automobile’s thermal environment,it is necessary to establish full-scale crew cabin model to get accurate results.